A cross-cultural perspective on the relationships among social media use, self-regulated learning and adolescents' digital reading literacy. (December 2021) - Chen, Jiangping; Lin, Chin-Hsi; Chen, Gaowei
Abstract: This study explored, from a cross-cultural comparative perspective, how use of social media (SM) impacted adolescents' digital reading literacy (DRL), and whether these two factors' relationship was mediated by self-regulated learning: i.e., knowledge of metacognitive strategies, enjoyment of reading, and reading self-concept. Several mediation models with multiple mediators were tested with a sample of data pertaining to 105, 430 15-year-old students from 3693 schools across six East Asian regions and nine Western countries that participated in the Programme for International Student Assessment (PISA) 2018. The results indicated that frequent SM use did not have any direct adverse impacts on adolescents' DRL; and indeed, small positive effects were observed in many countries/regions. The relationship between SM use and DRL was positively mediated by knowledge of metacognitive strategies, but not mediated by enjoyment of reading. In the Eastern regions, SM use did not have any significant indirect effect on DRL through reading self-concept, but in most Western countries, a positive indirect effect was observed. Highlights: Social media use did not have direct adverse impacts on digital reading literacy; Metacognition had positive mediating effects; Social media use negatively predicted reading enjoyment; Reading enjoyment generally did not significantly predict digital reading literacy; East-West differences were not obvious among the relationships.